THE ROLE OF COOPERATIVE INSURANCE IN THE INSURANCE SECTOR (Third Sector Social Economic Review, 2017)
Cooperative insurance is a type of insurance which combines the characteristics of insurance, the insured and the insurer. More than 750 thousand cooperatives can be found worldwide while there are only approximately 84 thousand cooperatives in Turkey. Insurance cooperatives, which can be considered as new in our country, can be found widely across the United States and later in Europe since the 1800's. Insurance cooperatives established in France, Switzerland and America attracted much interest. There are two insurance cooperatives operating in the Turkish insurance sector. The aim of this study is to evaluate the framework of cooperative insurance in the world and in Turkey.
Keywords: Insurance; Insurance Cooperatives; Turkish Insurance Industry